Mathematics Learning Design Using Dynamic Technology Scaffolding to Improve Student Learning Outcomes - Mahmuri, Hasnawati; Hamzah Upu; Hamda (International Journal of Technology and Education Research, 2025)
This study aims to develop and validate a mathematics learning design using Dynamic Technology Scaffolding (DTS) that meets the criteria of validity, practicality, and effectiveness to overcome learning obstacles for high school students in circle materials. The research uses the Educational Design Research (EDR) approach, with the following stages: Preliminary Research, Prototyping, Evaluation, and Implementation. Preliminary analysis identifies complex learning barriers, namely epistemological (abstraction difficulties) and ontogenic (weakness of prerequisites and affective motivation), which are exacerbated by didactic barriers. The DTS design is integrated into a Problem-Based Learning (PBL) model that focuses on three pillars: Physical Modeling, Exploratory Modeling, and Expressive Modeling using dynamic software (GeoGebra). The results of expert validation showed that the design was in the Very Valid category (average 3.77). Practicality was tested with an average of 1.78 (fully implemented) and very positive responses from teachers/students (79.11% and 92.85%, respectively). A significant increase in learning outcomes evidences effectiveness: the average pretest of 53.11 jumps to 92.65 on the Learning Outcome Test, with classical completeness of 89.92% (exceeding the 80% criterion). The normalized N-Gain score reached 0.86 (High category), confirming that the mathematics learning design using DTS is very effective as an adaptive intervention to bridge the Proximal Development Zone (ZPD) and improve students' mathematical skills.